The hidden and the familiar - Ho, Marcus Wei Kei (2018)
Most of us have a home or place that we are used to seeing on a daily basis and so often, we do not even see the objects in them anymore. Objects in our immediate environment hold no meaning because of such familiarity. Basically speaking, we are looking, but not seeing. The Hidden and The Familiar is an ongoing series that explores the nuances of modern life and the human role therein. It questions the absence of the human presence, yet acknowledges the presence of the absent.